Efficacy and safety of IL-17, IL-12/23, and IL-23 inhibitors for psoriatic arthritis: a network meta-analysis of randomized controlled trials - Gao, Shan; Xie, Xingxing; Fan, Ling; Yu, Linyuan (Frontiers in Immunology, 2025)
BackgroundPsoriatic arthritis (PsA) is a chronic inflammatory disease that impacts both the skin and joints. Currently, interleukin (IL)-17, IL-12/23, and IL-23 inhibitors have become integral components of PsA treatment regimens. Nevertheless, the comparative effectiveness of these IL-targeted therapies remains a subject of ongoing debate. This study employs a network meta-analysis (NMA) approach to systematically evaluate the therapeutic efficacy and safety profiles of various IL-17, IL-12/23, and IL-23 inhibitors.MethodsWe searched PubMed, Web of Science, and Embase for randomized controlled trials (RCTs) to identify eligible research articles. This NMA was implemented by Stata 14.0 software, with odds ratios (ORs) and 95% confidence intervals (CIs) serving as effect and safety measures to evaluate clinical efficacy and safety profiles. Drugs were ranked based on their efficacy and safety profiles using the surface under the cumulative ranking curve values, enabling a comprehensive comparative assessment of interventional strategies. The CINeMA (Confidence in Network Meta-Analysis) online tool was utilized to evaluate the confidence level of the NMA results.ResultsThis NMA included 22 RCTs and 9,241 patients. All intervention groups demonstrated superior efficacy to the placebo group. Based on efficacy endpoints and subgroup analyses, bimekizumab, secukinumab, and ixekizumab exhibited superior short-term efficacy. Notably, subgroup analyses suggested that tildrakizumab may represent a promising therapeutic option for PsA. Regarding safety and the risk of adverse events, all treatments demonstrated no significant differences compared to placebo, except bimekizumab 160 mg every 4 weeks (Q4W) (OR = 1.37, 95% CI: 1.08–1.74). There were no significant differences in terms of serious adverse events and upper respiratory tract infection. Bimekizumab 160 mg Q4W showed heightened risk of nasopharyngitis (OR = 2.30, 95% CI: 1.26–4.22).ConclusionsThis NMA showed that IL-17, IL-12/23, and IL-23 inhibitors demonstrated remarkable efficacy in attaining ACR20, ACR50, ACR70, and MDA after 12, 16, or 24 weeks of treatment. Among these, IL-17 inhibitors—particularly bimekizumab, secukinumab, and ixekizumab—exhibited notably pronounced therapeutic effects. However, bimekizumab showed a less favorable clinical safety profile compared to other biological agents. In contrast, secukinumab and ixekizumab demonstrated a favorable balance of relatively high efficacy and low risk when considering safety profiles.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251023787, identifier CRD420251023787.